Liver stiffness measurement and biochemical markers in Senegalese chronic hepatitis B patients with normal ALT and high viral load. - Papa Saliou Mbaye (Public Library of Science (PLoS), 2011)
Background and aims Despite the high prevalence of chronic hepatitis B (CHB) in Africa, few studies have been performed among African patients. We sought to evaluate liver stiffness measurement by FibroScan® (LSM) and two biochemical scores (FibroTest®, Fibrometer®) to diagnose liver fibrosis in Senegalese CHB patients with HBV plasma DNA load ≥3.2 log(10) IU/mL and normal alanine aminotransferase (ALT) values. Methods LSM and liver fibrosis biochemical markers were performed on 225 consecutive HBV infected Senegalese patients with high viral load. Patients with an LSM range between 7 and 13 kPa underwent liver biopsy (LB). Two experienced liver pathologists performed histological grading using Metavir and Ishak scoring. Results 225 patients were evaluated (84% male) and LB was performed in 69 patients, showing F2 and F3 fibrosis in 17% and 10% respectively. In these patients with a 7-13 kPa range of LSM, accuracy for diagnosis of significant fibrosis according to LB was unsatisfactory for all non-invasive markers with AUROCs below 0.70. For patients with LSM values below 7 kPa, FibroTest® (FT), and Fibrometer® (FM) using the cut-offs recommended by the test promoters suggested a fibrosis in 18% of cases for FT (8% severe fibrosis) and 8% for FM. For patients with LSM values greater than 13 kPa, FT, FM suggested a possible fibrosis in 73% and 70%, respectively. Conclusion In highly replicative HBV-infected African patients with normal ALT and LSM value below 13 kPa, FibroScan®, FibroTest® or Fibrometer® were unsuitable to predict the histological liver status of fibrosis.